Analisis Sifat Asam, Basa, dan Netral Menggunakan Bahan Sehari-hari : sebagai Media Pembelajaran IPA Sekolah Dasar - Delfina Delfina; Irma Irma; Nabila Azyan Busaynova (TA'DIBAN, 2026)
This study aims to describe the effectiveness of using concrete universal indicators in identifying the acid-base properties of everyday materials for elementary school students. The abstract concept of acids and bases is difficult for students to grasp without concrete visualizations in the classroom. The research method used was descriptive qualitative, involving practical experiments with lime, vinegar, toothpaste, and soap. The results showed that the universal indicators produced contrasting color changes: red for acids, green for neutral substances, and blue for bases.